Mastering Microsoft Exchange Server 2003 - Gerber, Barry (Sybex, 2003)
With this comprehensive guide, you’ll find out how to effectively install, configure, and manage Microsoft’s powerful messaging and collaboration server, Exchange Server 2007. From reducing the amount of spam your company receives to ensuring you have the right disaster recovery strategy, authors Barry Gerber and Jim McBee share their extensive real-world experience as they walk you step-by-step through each process. You’ll learn the essential techniques for planning and design, deployment, administration, maintenance, and troubleshooting.